2013
DOI: 10.3844/ajptsp.2013.20.30
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Effect, Incidence and Mechanism of Nevirapine Hepatotoxicity

Abstract: Nevirapine is a dipyridozepinone non nucleoside reverse transcriptase inhibitor approved for use in HIV-infected patients. Its efficacy has been well demonstrated in numerous clinical trials. It has activity against HIV-1 but does not have significant activity against HIV-2 or other retroviruses. Nevirapine is used as one of the components of highly active antiretroviral therapy in HIV patients and in the prevention of mother to child transmission of HIV. Reports have linked nevirapine containing highly active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Thus, reported NVP-induced hepatotoxicity comprises several clinical manifestations with varying degrees of severity including elevation of serum enzyme levels, bile duct obstruction and jaundice, hepatic necrosis, hepatitis and hepatic failure [49,51,[58][59][60][61][62]. NVP's associated hepatotoxicity in the clinics (case reports, clinical trials and cohorts' studies) has been reviewed in detail elsewhere [63]. A structured review of the literature (2005-2015) also revealed that NVP causes hepatotoxicity in pregnant patients, manifested as elevation of transaminases, rash, hepatitis, pruritus, abdominal pain, eosinophilia, encephalopathy, and jaundice [64].…”
Section: Nevirapinementioning
confidence: 99%
“…Thus, reported NVP-induced hepatotoxicity comprises several clinical manifestations with varying degrees of severity including elevation of serum enzyme levels, bile duct obstruction and jaundice, hepatic necrosis, hepatitis and hepatic failure [49,51,[58][59][60][61][62]. NVP's associated hepatotoxicity in the clinics (case reports, clinical trials and cohorts' studies) has been reviewed in detail elsewhere [63]. A structured review of the literature (2005-2015) also revealed that NVP causes hepatotoxicity in pregnant patients, manifested as elevation of transaminases, rash, hepatitis, pruritus, abdominal pain, eosinophilia, encephalopathy, and jaundice [64].…”
Section: Nevirapinementioning
confidence: 99%
“…Hepatotoxicity is one of the toxicological crimes associated with nevirapine (Rivero et al, 2007). Nevirapine hepatotoxicity is characterised by elevation of transaminases (AST and ALT) levels and hepatocytes necrosis (Elias and Brambaifa, 2013;. Efavirenz is associated with neuropsychiatric effects i.e central nervous system disturbances such as emotional instability, insomnia, hallucinations, impaired concentration and abnormal dreams (Jena et al, 2009).…”
Section: Toxicological Effects Of Non-nucleoside Reverse Transcriptasmentioning
confidence: 99%
“…Different types of antiretroviral combination therapies are available and use of a particular therapy depends on the tolerability, the cost, and the therapeutic objectives [3]. However, despite remarkable viral replication suppression, immune response restoration and decreased mortality, long-term HAART appears to be associated with the development of some toxicological effects like cardiotoxicity, hepatotoxicity and nephrotoxicity [4,5]. These have impaired therapeutic success via poor adherence, loss of serum HIV suppression, development of drugresistant HIV strains, and increased probability of illness progression [6].…”
Section: Introductionmentioning
confidence: 99%